Grosvenor family papers - Grosvenor, Edwin A. (Edwin Augustus), 1845-1936.; Grosvenor, Edwin Prescott, 1875-1930.; Grosvenor, Elsie May, 1878-1964.; Grosvenor, Gilbert Hovey, 1875-1966.; Grosvenor, Lilian Waters, 1852-1931.; Grosvenor, Melville Bell, 1901-1982.; Waters, Asa H. (Asa Holman), 1808-1887.; Waters, Elizabeth
Correspondence, diaries, speeches and writings, subject material, financial papers, printed matter, and personal miscellany of various members of the Grosvenor family, principally of Amherst and Millbury, Mass., and Washington, D.C.
The bulk of the papers relate to Gilbert H. and Elsie M. Grosvenor's personal and family life in Washington, D.C., Bethesda, Md., and Baddeck, Nova Scotia, Canada; his association with the National Geographic Society and the National Geographic Magazine; her community work including marches for women's suffrage and a Washington, D.C., drive for pure milk; their family ties with the Alexander Graham Bell and Taft families; their travels; and their associations with the Clarke School for the Deaf, the Volta Bureau, the George Washington University, and Amherst College. Also included are papers of Gilbert Grosvenor's parents, Edwin A. and Lilian Waters Grosvenor, relating to family matters, Edwin's work in medieval and Byzantine studies at Amherst College, and their travels in Europe and the Middle East. Other family members represented include Edwin Prescott Grosvenor, Melville Bell Grosvenor, and Lilian Waters Grosvenor's parents, Asa H. and Elizabeth Waters.
Prominent individuals represented by correspondence or other material include Herbert Baxter Adams, William Jennings Bryan, Alexander Graham Bell, Viscount James Bryce, Richard Evelyn Byrd, Joseph Conrad, George Constantine, Calvin Coolidge, Samuel Sullivan Cox, Wilcox Darwin, Amelia Earhart, Dwight D. Eisenhower, David Fairchild, Marian Fairchild, George W. Goethals, A.W. Greely, Abram S. Hewitt, Oliver Wendell Holmes, Jr., Henry Holt, Herbert Hoover, Julia Ward Howe, Helen Keller, Sinclair Lewis, Anne Morrow Lindbergh, Charles A. Lindbergh, George C. Marshall, Alexander Meiklejohn, Fridtjof Nansen, Florence Nightingale, Chester W. Nimitz, Robert E. Peary, W.M. Flinders Petrie, Auguste Piccard, Franklin D. Roosevelt, Theodore Roosevelt, Ernest H. Shackleton, Helen Herron Taft, William H. Taft, Ida M. Tarbell, Lowell Thomas, Delia C. Torrey, Lew Wallace. Susan E. Wallace, Woodrow Wilson, and Wilbur Wright.
Part II of the Grosvenor family papers contains correspondence of David and Marian Fairchild, material relating to the purchase and development of the Grosvenor family estate in Florida and to the development of the museum at Alexander Graham Bell's estate at Beinn Bhreagh, near Baddeck, Nova Scotia. Also includes material documenting Gilbert Grosvenor's conflict with National Geographic editor John Henry Hyde over the direction of the magazine. Correspondents include Oscar P. Austin and John Oliver La Gorce.
Library of Congress Prints and Photographs Division's Gilbert H. Grosvenor Collection of Photographs of the Alexander Graham Bell Family.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Herbert Baxter, -- 1850-1901.; Austin, Oscar P. -- 1848?-1933.; Bell, Alexander Graham, -- 1847-1922.; Bryan, William Jennings, -- 1860-1925.; Bryce, James Bryce, -- Viscount, -- 1838-1922.; Byrd, Richard Evelyn, -- 1888-1957.; Conrad, Joseph, -- 1857-1924.; Constantine, George; Coolidge, Calvin, -- 1872-1933.; Cox, Samuel Sullivan, -- 1824-1889.; Darwin, Wilcox; Earhart, Amelia, -- 1897-1937.; Eisenhower, Dwight D. -- 1890-1969.; Fairchild, David, -- 1869-1954.; Fairchild, Marian, -- 1880-1962.; Goethals, George W. -- 1858-1928.; Greely, A. W. -- 1844-1935.; Hewitt, Abram S. -- 1822-1903.; Holmes, Oliver Wendell, -- 1841-1935.; Holt, Henry, -- 1840-1926.; Hoover, Herbert, -- 1874-1964.; Howe, Julia Ward, -- 1819-1910.; Hyde, John Henry; Keller, Helen, -- 1880-1968.; La Gorce, John Oliver, -- 1880-1959.; Lewis, Sinclair, -- 1885-1951.; Lindbergh, Anne Morrow, -- 1906-2001.; Lindbergh, Charles A. -- 1902-1974.; Marshall, George C. -- 1880-1959.; Meiklejohn, Alexander, -- 1872-1964.; Nansen, Fridtjof, -- 1861-1930.; Nightingale, Florence, -- 1820-1910.; Nimitz, Chester W. -- 1885-1966.; Peary, Robert E. -- 1856-1920.; Petrie, W. M. Flinders -- 1853-1942.; Piccard, Auguste, -- 1884-1962.; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919.; Shackleton, Ernest Henry, -- Sir, -- 1874-1922.; Taft, Helen Herron, -- 1861-1943.; Taft, William H. -- 1857-1930.; Tarbell, Ida M. -- 1857-1944.; Thomas, Lowell, -- 1892-1981.; Torrey, Delia C; Wallace, Lew, -- 1827-1905.; Wallace, Susan E. -- 1830-1907.; Wilson, Woodrow, -- 1856-1924.; Wright, Wilbur, -- 1867-1912.; Bell family; Grosvenor family; Taft family; Amherst College; Clarke School for the Deaf; George Washington University; National Geographic Society (U.S.); Volta Bureau (U.S.); National geographic magazine; Community leadership -- Washington (D.C.); Deaf -- Education; Middle Ages